Malignant Diseases in Pregnancy - Ethical, Diagnostic and Treatment Challenge - Kesic, Vesna; Dimitrov, Goran (Македонско лекраско друштво /Walter de Gruyter GmbH, 2016)
The biological uniqueness of malignant tumors in pregnancy lies in the combination of uncontrolled growth of malignant tumors and controlled growth of fetoplacental complex in the same host. The risk of pregnancy associated with a malignant disease is approximately 0.1% (1 case per 1, 000 deliveries). According to results from one of the largest studies of malignant tumors in pregnancy, which involved almost thousand cases, the most frequent types were breast and cervical cancer, then melanoma, lymphoma and leukemia, gastric and rectal cancer, bone sarcoma and other sarcomas of the soft tissue. According to a Swedish retrospective study on cancer during pregnancy, the incidence rate is 37.4 cases per 100 000 deliveries. Pregnancy-associated malignant disease brings a range of specific problems, such as: difficulties related to diagnosis and staging of the disease; the risk of performing diagnostic and therapeutic procedures during pregnancy; counseling and treatment plan of pregnant women having malignant disease. The treatment plan of a pregnant patient with cancer has three possibilities: termination of pregnancy; postponement of treatment to reach fetal viability; treatment during pregnancy. The management of malignant disease during pregnancy may be highly dangerous or even fatal for the fetus. The treatment includes surgery, radio and chemotherapy. In malignant diseases during pregnancy, the prognosis is the same as in general population cancers of the same stage, localization and type. Termination of pregnancy is indicated in cases of, either high absorbed fetal radiation dose, or high grade, aggressive or metastatic cancer.